2023
DOI: 10.1021/acsami.2c20268
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stabilization of Cobalt-Free LiNiO2 with Niobium for Lithium-Ion Batteries

Abstract: Lithium nickel oxide (LiNiO2) is a promising next-generation cathode material for lithium-ion batteries (LIBs), offering exceptionally high specific capacity and reduced material cost. However, the poor structural, surface, and electrochemical stabilities of LiNiO2 result in rapid loss of capacity during prolonged cycling, making it unsuitable for application in commercial LIBs. Herein, we demonstrate that incorporation of a small amount of niobium effectively suppresses the structural and surface degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Ober et al also reported a similar finding, where the formation of intergranular Li x NbO y phases in LNO impeded the growth of its primary particles. 153 Hence, as previously emphasized, temperature conditions significantly influence niobium modification of LTMOs, and the possibility of an additional coating on the particle surface, including the primary particles themselves, should be considered.…”
Section: Dopingmentioning
confidence: 98%
See 1 more Smart Citation
“…Ober et al also reported a similar finding, where the formation of intergranular Li x NbO y phases in LNO impeded the growth of its primary particles. 153 Hence, as previously emphasized, temperature conditions significantly influence niobium modification of LTMOs, and the possibility of an additional coating on the particle surface, including the primary particles themselves, should be considered.…”
Section: Dopingmentioning
confidence: 98%
“…112,129,130,136,152 On the other hand, when the primary particles are compared, niobium appears to cause a significant reduction in their sizes. 59,119,120,128,153 Park et al showed an interesting study in this regard using different high-valence elements (Al 3+ , Nb 5+ , Ta 5+ , and Mo 6+ ) to dope LNO. 115 The samples were prepared by mixing Ni(OH) 2 , LiOH, and dopant precursor, with further calcination within the temperature range of 650 to 800 °C.…”
Section: Dopingmentioning
confidence: 99%
“…[11][12][13] Among these cathode materials, Co-free layered lithium nickel oxide (LiNiO 2 ) is undoubtedly the most distinctive, with a maximum theoretical specific capacity of 270 mAh g À1 at a higher-voltage plateau (3.8 V vs Li/Li þ ). [14][15][16][17][18][19][20] However, LiNiO 2 cathodes suffer from deterioration of the material surface and physical structure during cycling due to several reasons. During the synthesis of LiNiO 2 , a large amount of Ni 2þ cannot be oxidized to Ni 3þ .…”
Section: Introductionmentioning
confidence: 99%
“…Because the ionic radius of Ni 2þ (0.068 nm) is similar to that of Li þ (0.076 nm), Ni 2þ can easily occupy the original position of Li þ , leading to a phase transition and Li þ /Ni 2þ disorder. [15,19] Furthermore, Ni 4þ generated during the charging process reacts with the electrolyte, resulting in the loss of the oxygen lattice and structural collapse of the cathode surface. [18,20] Moreover, the tension induced by repetitive volume contraction and expansion during cycling may result in microcracks on the surface of the cathode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Facing up this challenge, recent years have seen a surge of efforts dedicated to the design and the stabilization of Ni-rich NMC materials using diverse approaches as the doping of active materials [19][20][21] , the design of surface coatings [22][23][24] or the use of additives for high voltage [25][26][27] . One strategy recently proposed to tackle instabilities at high potential is the use of so-called highly concentrated electrolytes (HCE) 28 .…”
Section: Introductionmentioning
confidence: 99%